2014
DOI: 10.1016/j.clim.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The autoimmune disease-associated transcription factors EOMES and TBX21 are dysregulated in multiple sclerosis and define a molecular subtype of disease

Abstract: We have identified a marked over-representation of transcription factors controlling differentiation of T, B, myeloid and NK cells among the 110 MS genes now known to be associated with multiple sclerosis (MS). To test if the expression of these genes might define molecular subtypes of MS, we interrogated their expression in blood in three independent cohorts of untreated MS (from Sydney and Adelaide) or clinically isolated syndrome (CIS, from San Francisco) patients. Expression of the transcription factors (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 46 publications
6
40
2
Order By: Relevance
“…When assessed together with our previously published cohort, the reduction in MS was highly significant (EOMES, p < 0.0001; TBX21, p < 0.0006; CCL5, p < 0.0001; Fig 1B, D, F). As we found in our original study [11], the expression of EOMES was tightly correlated with TBX21 and CCL5 (Fig 1G, r = 0.745, p = 8.792e-13; Fig 1H, r = 0.607, p = 5.692e-9 respectively for the new cohort assessed together). Overall, the median expression of EOMES for MS patients was 33% lower than controls (22% for TBX21; 21% for CCL5), and 64% of MS were in the bottom quartile of controls (41% for TBX21; 59% for CCL5) for the new cohort.…”
Section: Replication Of the Et Phenotype In New Cohortssupporting
confidence: 82%
See 4 more Smart Citations
“…When assessed together with our previously published cohort, the reduction in MS was highly significant (EOMES, p < 0.0001; TBX21, p < 0.0006; CCL5, p < 0.0001; Fig 1B, D, F). As we found in our original study [11], the expression of EOMES was tightly correlated with TBX21 and CCL5 (Fig 1G, r = 0.745, p = 8.792e-13; Fig 1H, r = 0.607, p = 5.692e-9 respectively for the new cohort assessed together). Overall, the median expression of EOMES for MS patients was 33% lower than controls (22% for TBX21; 21% for CCL5), and 64% of MS were in the bottom quartile of controls (41% for TBX21; 59% for CCL5) for the new cohort.…”
Section: Replication Of the Et Phenotype In New Cohortssupporting
confidence: 82%
“…Previously, we had shown that expression of EOMES and TBX21 were stable over time [11]. Here we have tested samples from a new cohort of patients and controls from two time points at least 6 months apart.…”
Section: Expression Of Eomes and Tbx21 Is Highly Heritablementioning
confidence: 99%
See 3 more Smart Citations